Electronic Word of Mouth and Its Effects on Consumer Decision-Making: Insights from an Extensive Literature Review - Siregar, Akhmad Irwansyah; Johannes, Johannes; Yacob, Syahmardi; Octavia, Ade (Ekonomis: Journal of Economics and Business, 2024)
This comprehensive literature review critically examines the pervasive influence of Electronic Word of Mouth (E-WoM) on consumer decision-making. Distilling insights from over a hundred scholarly articles spanning the last decade, this paper aims to map out how E-WoM impacts purchasing behaviors across diverse sectors. Methodologically, the review adopts a systematic approach to identify, analyze, and synthesize existing research, providing a robust evaluation of E-WoM's effects through both quantitative and qualitative lenses. Findings indicate that E-WoM significantly shapes consumer perceptions and buying decisions, moderated by source credibility, message sentiment, and consumer involvement. The study's major contributions include a proposed integrative model that links E-WoM dynamics with consumer decision-making processes, offering a nuanced understanding of the mechanisms at play. This model clarifies the pathways through which E-WoM exerts its influence and highlights the role of digital platforms in amplifying consumer voices. Furthermore, the paper identifies critical gaps in current research, particularly in the areas of cross-cultural variations and the influence of emerging technologies. By bridging these gaps, this review serves as a foundational resource for academics and practitioners alike, guiding future research trajectories and informing strategic marketing practices in the digital era.